Antibacterial and preliminary phytochemicals screening of theraxicum officinale - Hussain, I. (Journal of Pure and Applied Microbiology, 2014)
The antibacterial activity of different crude extracts of different parts of Theraxicum officinale including roots, stem and leaves and solvents (n-hexane, chloroform, ethyl acetate and methanol) against various human pathogens viz., Salmonella thphi (S. thphi), Escherichia coli (E. coli), Pseudomonas aeuroginosa (P. aeuroginosa). Staphylococcus aureus, were carried out. Among the extracts, methanolic extract of the roots fraction showed a maximum zone of inhibition (18 mm) against S. aureus, followed by leaves extract of maximum zone of inhibition (16 m), while the ethyl acetate fraction of leaves showed (15 mm) maximum zone of inhibition against S. auresus. While low activity of the stem extracts were recorded except for the methanolic extract with a maximum of zone of inhibition (13 mm) against S. typhi. In addition, the phytochemical analyses showed the presence of Phenols, Tannin, Alkaloids, Saponins and Flavonoids.